Using Restorative Practices to Create a School District that Cares - Boyd, Kim (2018)
Zero-tolerance became the rule in many school districts due to an increase in school-based violence, which served to silence student voices and led to the overrepresentation of minority students in discipline situations. Schools could adopt restorative approaches, but change cannot be sustained without fair processes at the district level. Thus, district policies should be aligned to restorative practices to increase the probability of district-wide success